Flakka-Induced Prolonged Psychosis - Craig Crespi (Case Reports in Psychiatry)
In South Florida, there has been a highly addictive new synthetic drug flooding the streets for people looking for a cheap high. Alpha-PVP, better known as Flakka, is an illegal substance that sells on the streets for as little as $5 a hit and delivers an instant high that can last from hours to days with lingering effects for weeks after it has been ingested. Although people use Flakka for its potential euphoric high, symptoms are known to easily escalate into frightening delusions, paranoid psychosis, extreme agitation, and a multitude of other altered mental states. According to the National Institute on Drug Abuse, Florida appears to be the nation’s hot spot for reports of Flakka. In this case report, a 17-year-old female with no prior psychiatric diagnosis presents to the hospital under a 72-hour involuntary placement for altered mental status with agitation and psychotic behaviors. After multiple days of symptomatic treatment with benzodiazepines and antipsychotics, the patient became coherent enough to give a history of a “friend” putting Flakka in her food at school as a joke. Although she continues to have residual symptoms including psychomotor agitation and slowing of cognition, she was alert, oriented, and able to be discharged home with proper follow-up.